Assessing Professional Development Training for Library Leader Candidates - Hegar Harini; Iis Dewi Lestari; Adisel Adisel; Yatha Yuni; Didin Hikmah Perkasa (LPPM STKIP Kusuma Negara, 2023)
Library, as a place holding pivotal roles to support instructions at schools, should be led by a competent and qualified leader. The present research is purposefully conducted to assess the training program intended for school library leader candidates. Qualitative method was employed by the implementation of CIPP (Context, Input, Process and Product) model. The data were collected through observations, interviews and document analysis. Snowball sampling technique was utilized to choose the research participants. The participants involved in this research were the head of assurance council, the head of training program, and the training partners. The present research indicates the following findings. Generally, the training is regarded as successfully implemented. To be more specific, 1) context evaluation assesses legal standing, objectives, and target of the training; 2) input evaluation assesses resource of the training; 3) process evaluation assesses trainee recruitment, teaching and learning process, and monitoring-evaluation of the training; and 4) product evaluation assesses cognitive, affective and skill domain of the trainees. The present research implies program segmentation for each level of education due to different problems encountered in reality. Training resource aspect also needs special attention.